Pengaruh Metode "Sabaq, Sabqi, Manzil" Terhadap Kemampuan Hafalan Santri di Rumah Tahfizh Al-Huda Pangkalpinang - Pratiwi, Wana Nur; Anwar, Muhammad Rofiq (LENTERNAL: Learning and Teaching Journal, 2023)
The purpose of this study is to test the influence of the methods “sabaq, sabqi, and manzil” on the ability of the centri. A quantitative research approach using correlational methods involves a population of entire centers of the Qur'an that is sampled using saturated sampling techniques. Data gathering techniques include lifting, centric evaluation, structured interviews, and documentation. Data analysis techniques use simple linear regression with the help of SPSS 22. The results of the study showed: 1) The values of the centri maturity for 4 weeks by applying the method “sabaq, sabqi, manzil” were at a satisfactory predicate at the interval of 75–85, where there were 17 centri with a percentage of 69.96%. See from the records of the ability of centrii maturity before and after the application of such methods that the centrian maturity that initially only sects maturity in a week 1⁄2 Juz increased to 1-2 Juz in the week. 2) There is no significant influence between the application of the methods “sabaq, sabqi, and manzil” and the ability of the centri. Showed with a titling result smaller than the table (0,924 < 1,708) means H0 accepted and Ha rejected. This can happen due to items on the lift that are not understood by the respondents, respondents answering with origins, different child memory abilities, and the presence of incoherent centri's muraja'ah.